Robust Password and Smart Card Based Authentication Scheme with Smart Card Revocation - 谢琪 刘文浩 王圣宝 胡斌 董娜 于秀源 (Shanghai jiao tong da xue xue bao, 2014)
User authentication scheme allows user and server to authenticate each other, and generates a session key for the subsequent communication. How to resist the password guessing attacks and smart card stolen attacks are two key problems for designing smart cart and password based user authentication scheme. In 2011, Li and Lee proposed a new smart cart and password based user authentication scheme with smart card revocation, and claimed that their scheme could be immunity to these attacks. In this paper, we show that Li and Lee＇s sctleme is vulnerable to off-line password guessing attack once the information stored in smart card is extracted, and it does not provide perfect forward secrecy. A robust user authentication scheme with smart card revocation is then proposed. We use a most popular and widely used formal verification tool ProVerif, which is based on applied pi calculus, to prove that the proposed scheme achieves security and authentication.